Epidemiological Profile of the Victims Involved in Road Traffic Accidents (RTA) and ICD-10 Classification Attending an Emergency Department: A Descriptive Study - Surendra Babu Darivemula; Sayeda Misbah Jabeen; Sai Revanth A. Surapaneni; Sakshi Piyush Rastogi; Harika Salodi; S Lakshmi Srujana; Nikhila Seelam; Sasidharan Shiga; S Karthik (Indian Journal of Community Medicine)
Road traffic injuries are the leading cause of death for children and young adults aged 5-29 years. They cause approximately 1.3 million deaths every year, with 20 to 50 million more people suffering nonfatal injuries and many incurring a disability as a result of their injury. A retrospective record-based descriptive study was performed to analyze the epidemiological profile of the patients attending with road traffic accidents (RTA) to emergency/casualty department in a tertiary care hospital. The purposive sample from the last 7 months with those affected from RTA cases came to casualty and undergone treatment during the study duration and the exclusion criteria were brought dead patients. Out of 397 victims, 309 (77.8%) were male and 88 (22.2%) were female and mean age with SD 37.19 ± 13.9 years. Majority 143 (36.0%) had self-fall, 64 (16.1%) 2-wheeler vs pedestrian, 63 (15.9%) 2-wheelers vs 4-wheeler, 55 (13.9%) under 2-wheelers vs 2-wheeler. Majority were happened on Saturday 60 (15.1%), Sundays 71 (17.9%) and the rest on an average of 50 incidents in a day; out of them, the incident happened at evening 98 (24.7%) night 136 (34.2%) morning 109 (27.5%), and in the afternoon time 54 (13.6%), respectively. Accidents have male predominance, with more victims from adults and middle age 21-40 years. Most common category of the victim was motorcycle rider, followed by pedestrians, and as per ICD-10 classification, the common mechanism of incident happened was motorcycle rider noncollision transport accident (Code: V28).